2020
DOI: 10.3390/dj8030084
|View full text |Cite
|
Sign up to set email alerts
|

The Association between D-Dimer and Prognosis in the Patients with Oral Cancer

Abstract: D-dimer levels are reported to relate with tumor stage, prognosis, and lymph node involvement, as well as overall survival (OS) in patients with solid tumors. The purpose of this study was to investigate association between the value of D-dimer and the prognosis of oral cancer (OC). We designed a retrospective cohort study and enrolled a sample of patients who were diagnosed with OC and treated with surgery and/or radiotherapy. The predictor was the D-dimer and outcome variable was OS. Other variables included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The causes of increased D-dimer include advanced age, tumor, surgical operation, infection, and so on. More importantly, D-dimer predicts significantly different overall survival rate in oral cancer patients with a cut-off value of 0.7 μg/mL (31). A high preoperative D-dimer level in patients with oral squamous cell carcinoma suggests a poor prognosis, and the difference of D-dimer between preoperative and postoperative is related to the type of operation (32).…”
Section: Discussionmentioning
confidence: 96%
“…The causes of increased D-dimer include advanced age, tumor, surgical operation, infection, and so on. More importantly, D-dimer predicts significantly different overall survival rate in oral cancer patients with a cut-off value of 0.7 μg/mL (31). A high preoperative D-dimer level in patients with oral squamous cell carcinoma suggests a poor prognosis, and the difference of D-dimer between preoperative and postoperative is related to the type of operation (32).…”
Section: Discussionmentioning
confidence: 96%
“…D-dimer is widely used to diagnose disseminated intravascular coagulation, thromboembolism, and myocardial infarction. Recently, it has been reported that high levels of D-dimer can be detected across certain types of cancers, 12 such as lung cancer, 5 oral cancer, 13 prostate cancer, 14 and colorectal cancer. 15 Our research initially demonstrated that D-dimer levels were significantly higher among patients with AFPGC compared with healthy volunteers and AFP-negative GC ( Figure 1A ).…”
Section: Discussionmentioning
confidence: 99%
“… 15 17 Traditionally, invasion and metastasis are late events in the progression of oral cancer. 17 19 At present, it is believed that during the early stage of oral cancer, tumor cells have begun to infiltrate, 20 , 21 but the regulatory mechanism unclear.…”
Section: Discussionmentioning
confidence: 99%